Great debates in tort law - Morgan, Jonathan (London : Hart Publishing, 2022)
Exploring the key discussions and arguments in tort law, this book enables students to get a deeper and more rounded understanding of the subject. Part of the Great Debates series, it is an engaging introduction to the more advanced legal concepts, such as negligent breach of duty and vicarious liability. Each chapter is structured around questions and debates that provoke deeper thought. It features summaries of the views of notable experts on key topics and each chapter ends with a list of further reading. This book is ideal for use by ambitious students alongside a main course textbook, encouraging them to think critically, analyse the topic and gain new insights. The development of these skills and the discursive nature of the series, with an emphasis on contentious topics, means the book is also useful for students when preparing their dissertations. Suitable for use on courses at all levels, this book helps students to excel in coursework and exams..
1. The Purposes of Tort Law --2. Negligence: Duty of Care: The Contours of Liability --3. Negligent Breach of Duty --4. Causation --5. Strict Liability: Defective Products and Breach of Statutory Duty --6. Nuisance --7. Vicarious Liability --8. Defences --Further Reading.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Law; United States